Winter University 2017. Urban rivers as a part of sustainable development - Nuyanzina, Valeria; Kosolapova, Anastasia (project baikal, 2017)
The article presents proposals worked out by the international teams that took part in the 18th session of International Baikal Winter University of Urban Planning. The session focused on small rivers rehabilitation as a part of sustainable development. Through the case study of the Ushakovka River in Irkutsk, the teams proposed new ideas of riverfront development, which can be also applied to other small rivers.
Keywords: Winter University of Urban Planning Design; small rivers rehabilitation; territorial development scenarios; quality of urban environment; urban studies